N1 responses to images of hands in occipito-temporal event-related potentials - Espírito Santo, Miguel Granja; Maxim, Octavian Sorin; Schürmann, Martin (Elsevier, 2017)
Hands, much like faces, convey social information, instructions and intentions to an observer. While the neural processes of face perception have been widely studied, it was only recently that fMRI identified occipito-temporal areas sensitive to static images of hands as body parts. To complement these studies with fine-grained timing information, we measured event-related EEG potentials (ERPs) from 33 subjects who were presented with static images of hands versus faces, whole bodies, and inanimate objects as controls. Already at N1 latency, ~ 170 ms, hand-related ERP patterns were manifest in two results: (1) significant differences in amplitudes for images of hands versus bodies in occipito-temporal N1 responses; (2) left lateralization of responses to images of hands, and also of the difference waveforms (hands minus bodies), quantifying hand-related responses. In line with fMRI studies of hand-sensitive areas distinct from extrastriate body area (EBA), the current findings provide electrophysiological evidence for hand-sensitive brain activation, occurring at a similarly early latency as N1 responses to faces.